NEW POSSIBILITIES OF STATIN THERAPY IN ARTERIAL HYPERTENSION - E. M. Khurs; A. V. Poddubnaya; M. G. Evsina; E. M. Futerman; O. G. Smolenskaya (Рациональная фармакотерапия в кардиологии, 2016)
Background. Effects of statins on cardiovascular end points are well-known. To study the impact of statins on structural and functional heart remodeling in patients with arterial hypertension (HT) seemsto be topical.Aim. To study the effect of statins on cardiac remodeling in patients with HT.Materials and methods. 120 patients with HT of 1 degree were included into the study: 56 men, 64 women, aged 52.4±10.23. Patients were randomized into 4 treatment groups: Group A1 (angiotensin converting enzyme (ACE) inhibitors + diet), group A2 (ACE inhibitor + fluvastatin), group B1 (angiotensin II receptor antagonist (ARA II) + diet), group B2 (ARAII + fluvastatin). Transthoracic echocardiography with calculation of standard left ventricle (LV) remodeling indices was performed.Results. The most important prognostic markers of LV remodeling were revealed. They were a basis for definition of 3 types of early LV remodeling: type 1 — compensated, type 2 — adaptive, 3 type — maladaptive. After 6 months of treatment a number of patients in group A1 with type 2 and type 3 of LV remodeling reduced less (2%, p=0.02 and 4%, p=0.04, respectively) than this in group A2 (14%, p=0.04) and 4%, p=0.04, respectively). A number of patients with type 1 (compensated) of LV remodeling increased by 18% (p<0.001) in group A2, and by 6%, (p=0.03) in group A1. After the treatment a number of patients with type 3 and type 2 of LV remodeling decreased (p<0.001 and p=0.04, respectively) in groups B1 and B2 while a number of patients with type 1 of LV remodeling increased (p<0,001). A number of patients with type 1 of LV remodeling increased and this with type 3 of LV remodeling decreased in group B2 more prominently in comparison with group A2 (p=0.03; p=0.01, respectively).Conclusion. Statins in patients with HT have cardioprotective effect that does not depend on basic antihypertensive therapy and total cholesterol level. In these patients combination of statins with ARA II has better cardioprotective effect than this with ACE inhibitors.